An Overview of Recreation and Parks Professional Preparation Programs in Higher Education: 探討大專院校的康樂及公園管理專業課程 - MAK, Jennifer Y. M. (Asian Journal of Physical Education & Recreation, 2000)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The purpose of this paper is to give an overview of recreation and parks professional preparation programs in higher education. This paper will (a) help to understand the framework of recreation and parks professional preparation programs, (b) discuss the factors which influence the professional preparation outcomes, and (c) help to identify future research needs. The discussion is based on the framework for studying professional preparation programs by Stack, et al. (1986). The key element of the framework for studying recreation and parks professional preparation programs is the recreation and parks professional preparation environment which was the product of external, internal and intra-organizational influences. The recreation and parks professional preparation environment influences the design of education process, which intends to achieve recreation and parks professional preparation outcomes. 本文章旨在探討大專院校的康樂及公園管理專業課程，內容計有(a)幫助了解康樂及公園管理專業課程的架構；(b)影響專業發展的因素；及(c)策劃未來的研究路向。討論內容主要是以Stack (1986)等學者所倡導的架構作為參考，並分析各元素的內因和外因對專業課程的影響，從而建議康樂及公園管理專業課程在敎育範疇上的改革。